Performance of ber (Ziziphus mauritiana L.) based hortipastoral system as influenced by pruning intensities, pastures and weather - Kumar, Sunil; Ram, S.N. (Indian Journal of Agroforestry, 2020)
Ber Cv. Gola based hortipastoral system was studied in four consecutive year (2001-2 to 2004-5) Involvolng ber tree (10 year old) with three pruning intensities to utilize interspaces through different pasture combinations for optimization of system productivity. Medium pruned tree (40cm height of secondary branches) produced maximum fruit Yield (26.3 kg/tree) followed by light (23.4 kg/tree) and severe pruned tree (18.3 kg/tree). However, the pasture production was significantly influenced by pruning intensities and severely pruned tree produced significantly higher pasture (4.05 t DM/ha) as compared to medium (4.02t DM/ha) and light pruned tree (3.77 t D M/ha). Among pasture combinations Guinea grass + Stylosanthes hamata produced significantly higher forage (6.33 t DM/ha) as compared to Dinanath + Guinea grass + S.hamata (5.06 t DM/ha), Dinanath + S. hamata (3.28 t DM/ha) and natural pasture (1.32 t DM/ha). Rainfall during sprouting phase (June- August) favoured yield and quality of ber while that during flowering phase (September) adversely affected the same. The understorey pasture combination did not Influence the quality of ber.